SEJARAH MUSLIM ROHINGNYA - Sriliza Sriliza; Yusrain Yusrain; Elsa Mulya Karlina (Adisam Publisher, 2025)
This jurnal discusses the long history of the Rohingya Muslim community living in the Rakhine region, Myanmar. Their history as a marginalized ethnic minority group involved in ongoing socio-political conflicts in the country is the main focus of this research. Through a historical approach, this Jurnal analyzes the origins of the Rohingya ethnic group, their interactions with Myanmar kingdoms in the past, and the impact of political changes and discriminatory policies on their status as citizens. This research also highlights the social and humanitarian struggles experienced by Rohingya Muslims, as well as how they face the challenges of a massive exodus due to violence that occurred in the last decade. By referring to various historical sources and international reports, this jurnal aims to provide a deeper understanding of the historical and humanitarian situation faced by the Rohingya Muslim community